Measurement of Lipid Peroxides in Apo B-Containing Lipoprotein Fraction in Plasma - Shishino, Koji; Murase, Mitsuharu; Saheki, Shuichi; Takeuchi, Nozomu; Tokunaga, Kenji (Japanese Journal of Clinical Chemistry, 1996)
Measurement of lipid peroxides (LPO) in apo B-containing lipoproteins is reported. LPO was measured by fluorometry after thiobarbituric acid reaction in immunoprecipitates with antiapo B serum. Inter- and intra-assay precisions were below 6.0% and 7.0% CV, respectively and the normal reference range was 0.30-1.52nmol/ml (±2SD). Correlation between the proposed method and the current phosphotungstic acid/magnesium chloride method was good; (r=0.931, y=0.864x-0.05). The distribution of plasma LPO was 21.8% to the apo B-containing fraction and 78.4% to the non-apo B fraction. Diabetes mellitus patients with vascular complications had significantly higher values and those without complications had slightly higher LPO levels in plasma and LDL or HDL fraction compared to those normal subjects